Distribution of miRNA expression across human tissues - Ludwig, Nicole; Meder, Benjamin (Nucleic acids research, 2016)
Abstract. We present a human miRNA tissue atlas by determining the abundance of 1997 miRNAs in 61 tissue biopsies of different organs from two individuals coll
Gesehen am 12.09.2019